A Seizure Attributed to Ofloxacine in a Woman Undergoing Detoxification for Alcohol Dependence. (21st January 2010) - Lahmek, Pierre; Michel, Laurent; Meunier, Nadine; Aubin, Henri-Jean
Abstract : Objective . To report one case of seizure following administration of ofloxacin. Case Summary . A 38-year-old woman with alcohol dependence but no prior history of seizure disorder admitted in our inpatient alcohol detoxification program was prescribed ofloxacin four days after admission for a lower urinary tract infection. She was currently prescribed diazepam 30 mg per day. This treatment was continued without modification following admission. Forty eight hours after starting ofloxacin and after receiving five doses of oral ofloxacin, the patient experienced a seizure. Ofloxacin treatment was stopped and no further seizures occurred. Neurological examination of the patient, laboratory tests, computerized tomography with contrast enhancement and electroencephalography did not detect any abnormalities. Up to the last consultation, six months after admission, the patient has reported no recurrence of the seizure. Discussion . Quinolone antibiotics vary in their ability to induce seizures, with ofloxacin having one of the least potentials. In the present case, the seizure could be attributed in all probability to taking ofloxacin; since she had no previous history of seizures, she did not present an alcohol withdrawal syndrome, benzodiazepine treatment was not modified, the seizure occurred 48 h after taking ofloxacin, but seven days after stopping drinking, no alternative aetiologies for the seizure could be identified and no seizure recurrence was reported over the following seven months. Of reported cases of seizures in patients treated with fluoroquinolones, none concerned patients with alcohol dependence or patients treated with benzodiazepines. Conclusions . The present case alerts us to the possibility that seizures may occur in alcohol dependent patients treated with benzodiazepines who concomitantly prescribed a fluoroquinolone. These widely-used antibiotics should thus be prescribed with caution to patients undergoing detoxification for alcohol dependence, particularly if they are also taking benzodiazepines, irrespective of whether they have a previous history of seizures or not.